Underwear Rules for Preventing Sexual Violence - Vina Vitniawati; Iis Sopiah Suryani suryani; Mia Nisrina Anbar Fatin; Novitasari Tsamrotul Fuadah; Hairani Hairani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Child sexual violence is a phenomenon that requires joint attention because it affects all aspects such as the growth and development of children both physically, emotionally and psychologically so that it requires prevention efforts.program to teach how to provide sexual education for early childhood as an effort to prevent sexual violence in children.Madrasah Ibtidaiyah Permata Bangsa does not yet have a program andhave not received information about efforts to prevent child sexual violence including the Underwear Rules program. So it is necessary to increase knowledge about how to prevent sexual violence in children. The method in Community Service is health education about reproductive health and sexual violence. For the impact of sexual violence and its handling, it will be carried out through seminars involving psychologists which are carried out in a hybrid manner and methods of playing with children regarding underwear rules. Before and after implementation, pretest and posttest measurements were carried out to measure the understanding of teachers, parents and children regarding efforts to prevent sexual violence in children. Keywords: Community Service, Underwear Rules, Sexual Violence